Gaya Bahasa Pada Lirik Lagu Westlife Dalam Album Coast To Coast - Ratih Puspa Ningrum (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2024)
This research is entitled The Language Style of Westlife Songs Lyrics in the Coast to Coast Album.  The purposes of this research are: (1) to describe a lyric picture containing the language style of Westlife song in the Coast to Coast album, (2) to describe a meaningful picture from the language style on Westlife song lyric in the Coast to Coast album. The research method used in this research is the qualitative research method of descriptive type with an objective approach. For the data collection technique, the author used the pay-attention technique and note-taking technique. In contrast, the data analysis technique used is the data analysis technique by Miles and Huberman: data condensation, data display, and drawing conclusion and verification. The result of this research is: (1) the lyric containing the repetition language style based on the type, are epigenesis, anafora, mesodiplosis and the hyperbole language style on Westlife song in the Coast to Coast album, (2) the denotative meaning and connotative meaning from the repetition language style and the hyperbole language style on Westlife song lyric in the Coast to Coast album.